Attached to the world : on the anchoring and strategy of Dutch foreign policy. - Knapen, Ben; Arts, G. (Gera); Kleistra, Yvonne, 1961-; Klem, Martijn; Rem, Marijke (Wrr Ser., 2011)
Few other countries are so interrelated with the World around us in political, economic, and social respects as the Netherlands. This means that the Dutch government needs to be alert in its response to the risks and opportunities presented by a rapidly changing world. Addressing this issue, The Scientific Council for Government Policy (WRR) is offering some reflections in this report, guided by the question how the Netherlands can develop a foreign policy strategy that matches the changing power relations in the world and the radically changed character of international relations.